Persistent otorhinolaryngological symptoms in patients following COVID-19 infection - Regmi, Deepak; Manandhar, Naresh (Journal of Kathmandu Medical College, 2022)
Background: Patients having coronavirus disease 2019 (COVID-19) may have persistent symptoms even after weeks or months of recovery. Although there are several studies on persistence of general symptoms, research primarily focussing on post COVID otorhinological symptoms are scarce. Objective: The aim of study was to assess the persistent otorhinolaryngological symptoms among the patients within a period of three months of recovery from COVID -19 infection. Methods: An analytical cross-sectional study was carried out in the ENT OPD of Kathmandu Medical College Teaching Hospital Nepal from July 2021 to September 2021. Ninety-one consecutive patients who recovered from COVID-19 were evaluated. The frequency of otorhinolaryngological manifestations at the time of presentation and during the active COVID-19 illness were interpreted and classified as nasal, aural, and throat symptoms. Results: The commonest persistent nasal symptoms were the nasal obstruction in 15 out of 43 patients during COVID (15/43, 34.88 %), followed by nasal discharge (2/12, 16.66%), loss of smell (12/73, 16.43%), and frontal headache (8/40, 20%). Twenty patients had persistent aural symptoms and all of them had tinnitus (8/8, 100%) followed by earache (4/7, 57.14%), hearing loss (3/6, 50%) and dizziness (4/14, 28.57%). Thirty-four patients had persistent throat symptoms. The most common was sore throat (23/49, 46.93%) followed by itching (4/13, 30.76%), hoarseness (3/25, 12%), and dry cough (3/52, 5.7%). Conclusion: Many ENT OPD patients had variable nasal, aural, and throat complaints at the time of infection which was still persisting in majority of them within three months of recovery from COVID-19.